Talenta Prestatif: Membangun Bakat dan Minat Berprestasi - Riska Amalia; Masduki Asbari; Novia Anisawati (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to identify talents who excel through the courage to take risks and decisions. This study uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's YouTube channel entitled "Conversation on the Achievements of Indonesian Talents" presented by the Minister of Education, namely Nadiem Makarim. The results of this study explain that several talents who excel in Indonesia were able to dare to choose and take risks and decisions when they felt it was very easy to fail because of their limitations, but they succeeded because of their own enthusiasm. Even though some individuals have all limitations, their courage to take risks and the courage to fail is something unique. The difference between mediocrity and success is courage itself, success is not seen from your GPA or how obedient you are to your teacher. The courage to take risks and make decisions for things we like can make us achievers.